2010
DOI: 10.1111/j.1540-8159.2010.02807.x
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation for Paroxysmal Atrial Fibrillation: A Randomized Comparison between Multielectrode Catheter and Point-by-Point Ablation

Abstract: Clinical success rates of PV isolation are similar when using multipolar circular PV ablation catheter and point-by-point ablation with a three-dimensional (3D) navigation system in patients with PAF, and results in shorter procedural and fluoroscopic times with a comparable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 17 publications
4
42
0
5
Order By: Relevance
“…These "single-shot" techniques were designed to create a circular ablation lesion around the PVs after the appropriate positioning of the ablation catheter at the ostium or at the antra of each PV. A number of studies have demonstrated comparable levels of success and safety profile, but shorter procedure times with these simplified methods than with the conventional point-by-point ablation [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…These "single-shot" techniques were designed to create a circular ablation lesion around the PVs after the appropriate positioning of the ablation catheter at the ostium or at the antra of each PV. A number of studies have demonstrated comparable levels of success and safety profile, but shorter procedure times with these simplified methods than with the conventional point-by-point ablation [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the data confirmed the short fluoroscopy and procedure times with PVAC that have been reported by other investigators in various study settings. 9,10 To our knowledge, the duration of follow-up in our cohort is the longest reported to date for PVAC, particularly in patients with persistent/long-lasting persistent AF. The rates of freedom from PAF after 12 months of follow-up were highly similar to those reported for the technology in a recent meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,8 However, the number of patients in published reports remains limited; there are few publications that outline experiences with PVAC under conditions of actual care, and comparisons with Carto ® (Biosense Webster, Inc., Diamond Bar, CA, USA) and NavX™ (St Jude Medical, Inc., Saint Paul, MN, USA) are rare. 9,10 In addition, there are few data available on the technology in patients with persistent or long-lasting AF. As with all recent technologies, more studies with long-term follow-up are needed.…”
Section: Spitzer Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In other study comparing efficacy of PVAC vs. CARTO procedure AF recurrence was documented in 23% and 29% of patients in the PVAC and CARTO groups, respectively (p = 0.8), they also found significantly shorter procedural and fluoroscopic times in the PVAC group (p < 0.0001) [12].…”
Section: Procedures Performance Of the Pvacmentioning
confidence: 99%